Polypill for the prevention of cardiovascular disease (PolyIran): study design and rationale for a pragmatic cluster randomized controlled trial. (December 2015) - Ostovaneh, Mohammad Reza; Poustchi, Hossein; Hemming, Karla; Marjani, Hajiamin; Pourshams, Akram; Nateghi, Alireza; Majed, Masoud; Navabakhsh, Behrouz; Khoshnia, Masoud; Jaafari, Elham; Mohammadifard, Noushin; Malekzadeh, Fatemeh; et al.
Background: The complexity of treatment regimens, costs and pill burden decrease the medication adherence and contribute to shortfall in cardiovascular preventive drug coverage. The polypill, a fixed dose combination pill of established drugs, is expected to increase adherence and reduce the costs whilst preventing major cardiovascular events (MCVE). Design and methods: The PolyIran trial is a pragmatic cluster randomized trial nested within the Golestan Cohort Study (GCS). Subjects were randomized to either non-pharmacological preventive interventions alone (minimal care arm) or together with a polypill (polypill arm) comprising hydrochlorothiazide, aspirin, atorvastatin and either enalapril or valsartan. This study benefits from the infrastructure of the primary health care system in Iran and the interventions are delivered by the local auxiliary health workers (Behvarz) to the participants. The primary outcome of the study is the occurrence of first MCVE within five years defined as non-fatal and fatal myocardial infarction, unstable angina, sudden death, heart failure, coronary artery revascularization procedures, and non-fatal and fatal stroke. Trial status: From February 2011 to April 2013, 8410 individuals (236 clusters) attended the eligibility assessment. Of those, 3421 in the polypill arm and 3417 in the minimal care arm were eligible. The study is ongoing. Conclusion: The infrastructure of GCS and the primary health care system in Iran enabled the conduct of this pragmatic large-scale trial. If the polypill strategy proves effective, it may be implemented to prevent cardiovascular disease in developing countries.